Exploring Suitable Nitrification Inhibitor in an Intensively Cultivated Greenhouse Soil and Its Effect on the Abundance and Community of Soil Ammonia Oxidizers - Xing Liu; Yanan Cheng; Ying Zhang; Fei Wang; Yonggang Li; Changwei Shen; Bihua Chen (Agronomy)
The application of nitrification inhibitors (NIs) is an effective way to reduce soil nitrogen (N) losses and increase crop N uptake. Yet, the efficacy of NIs commonly varies with dosages, crop systems and soil environmental conditions. Hence, clarifying the suitable type and dosage of NIs is extremely important for structuring the best N management regime at a regional scale. Here, based on microcosm experiments, we evaluated the influence of three widely used NIs [Dicyandiamide, DCD; 3,4-Dimethylpyrazole phosphate, DMPP; 2-chloro-6-(trichloromethyl) pyridine, Nitrapyrin] on the nitrification activity of an intensively cultivated greenhouse soil. The results showed that both DCD and DMPP imposed a transient inhibition on nitrification (less than five days) regardless of the dosages applied, and, on the contrary, Nitrapyrin presented a persistent suppression, with a longer duration of the inhibition action by a higher dosage. Accordingly, the incorporation of Nitrapyrin at 2% of the applied N rate (w/w) is a recommendable dosage for local intensive greenhouse production. Further, we assessed the influence of various dosages of Nitrapyrin incorporation (0%, 0.25%, 0.5%, 2% and 5%) on the abundance and community of three groups of soil ammonia oxidizers [i.e., ammonia-oxidizing archaea (AOA), ammonia-oxidizing bacteria (AOB) and completely ammonia-oxidizing bacteria (Comammox Nitrospira)] by qPCR and high-throughput amplicon sequencing. Nitrapyrin incorporation strongly lowered both the AOB and Comammox Nitrospira abundances and their community richness even at the lowest dosage. Nitrapyrin incorporation also significantly altered the community structure of all of the tested ammonia oxidizers, and the average relative abundance of some major community members (i.e., the Nitrososphaerales Clade Nitrososphaera, Nitrososphaerales Clade A, Nitrosospira briensis Clade, Nitrosospira multiformis Clade, Comammox Nitrospira Clade A.2 and Comammox Nitrospira Clade A-associated) obviously responded to Nitrapyrin incorporation. Overall, our findings indicated that AOB and Comammox Nitrospira were more sensitive to Nitrapyrin incorporation as compared with AOA. The results obtained here highlight the importance of optimizing the type and dosage of NIs for N fertilization management in intensive greenhouse vegetable production. Nitrapyrin incorporation inhibits soil nitrification probably by suppressing the Nitrosospira multiformis Clade in the AOB community at the level tested herein.